Efficacy and safety of a novel 785 nm picosecond neodymium-doped yttrium aluminum garnet laser for the treatment of facial benign pigmented lesions in Asian skin: a pilot study - Ji Yeon Hong; Sun Hye Shin; Young Gue Koh; Joon Seok; Kui Young Park (Journal of Dermatological Treatment)
Background and Objectives Benign pigmented lesions and a general uneven tone in people with skin of color are growing issues that have been presented to dermatologists. To the best of our knowledge, this is the first controlled study to examine the efficacy and safety of using the newly introduced 785 nm neodymium-doped yttrium aluminum garnet (Nd:YAG) picosecond laser to treat facial benign pigmented lesions in Asian patients with diffractive lens array.Materials and Methods A 785 nm Nd:YAG picosecond laser was used to treat 15 healthy female volunteers older than 18 years who had Fitzpatrick skin types II–IV and facial benign pigmented lesions. Each volunteer received five weekly treatments in dual modes. The clinical improvement was assessed by independent investigators and by objectively measuring the melanin index.Results After the treatment, the melanin and erythema indices decreased, and the pigmented lesions showed clinical improvements. No serious adverse effects were observed during the study period.Conclusions A 785 nm Nd:YAG picosecond laser may be safe and effective in treating facial benign pigmented lesions in Asian skin.